Analisis Pengaruh Kepuasan Pengguna Sistem Informasi Akademik Universitas Muhammadiyah Palembang Menggunakan Model Delone dan Mclean - Anggi Sefti Utami; Dian Hafidh Zulfikar; Sri Rahayu (APTIKOM SUMSEL, 2022)
SIMAKAD is applied to obtain all information related to activities in the computerized academic field within the Muhammadiyah University of Palembang. One of the keys to the success of an information system can be seen from user satisfaction with the system itself. SIMAKAD at Muhammadiyah University of Palembang there are several problems such as response from the system, frequent delays in the use process, profile photos do not appear, the help menu on the system experiences delays in response. This study uses the DeLone and McLean model. This study aims to determine what factors affect user satisfaction (User Satisfaction). The data obtained in the form of questionnaire data collected from respondents amounted to 350 respondents. The analysis used is multiple linear regression which includes partial t-test, namely the system quality variable obtained tcount of 4.288, information quality variable obtained tcount of 4.724, service quality variable obtained t-count of 4.652 and the F test simultaneously obtained Fcount of 75.593. From the results of these tests, it can be stated that the 4 hypotheses proposed have a significant influence on user satisfaction of academic information systems at Muhammadiyah University of Palembang.